The Influence of Service Quality, Promotions, and Ease of Use of BSI Mobile on the Interest of Generation Z Students at The Faculty of Sharia IKHAC Mojokerto - Alamsyah, Lutvi; Safitri, Firdana (Danadyaksa: Post Modern Economy Journal, 2024)
Sharia mobile banking is one of the banking services offered through digital technology. because m-banking services can always meet all the needs of society in today's digital era Prioritizing mobility, mobile banking can be said to be developing the fastest. The formulation of the problem in this research is whether there is an influence of service quality, promotions, and ease of use on the Interest of Generation Z Sharia students 2020-2021 Islamic Boarding School Institute KH. Abdul Chalim (IKHAC) Mojokerto using payment mobile banking in Sharia banking. This research aims to determine the influence of service quality on the interest of Generation Z students at the Sharia Faculty, KH Islamic Boarding School Institute. Abdul Chalim Mojokerto using BSI mobile. This type of research is quantitative with a sample of 69 respondents using SPSS version 22, based on the results of research and tests carried out, it shows partially service quality, promotions, and ease of use influence the interest of Generation Z students at the Institute's sharia faculty KH Islamic Boarding School. Abdul Chalim Mojokerto. Meanwhile, it is simultaneously variable service quality, promotions, and ease of use influence interest.